Strand specific cleavage of phosphorothioate-containing DNA by reaction with restriction endonucleases in the presence of ethidium bromide. - Sayers, J R (1988)
A method for achieving strand specific nicking of DNA has been developed. Phosphorothioate groups were incorporated enzymatically into the (-)strand of M13 RF IV DNA. When such DNA is reacted with restriction endonucleases in the presence of ethidium bromide nicked DNA (RF II) is produced. All of the restriction enzymes tested linearised phosphorothioate-containing DNA in the absence of this dye. The strand specificity of the reaction was investigated by employing the ethidium bromide mediated nicking reaction in the phosphorothioate-based oligonucleotide-directed mutagenesis method. The mutational efficiencies obtained were in the region of 64-89%, indicating that these restriction enzymes hydrolyse the phosphodiester bond at the cleavage site of the unsubstituted (+)strand.